2019
DOI: 10.1017/s0033291719002903
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of irritability in adolescents: longitudinal associations with psychopathology in adulthood

Abstract: BackgroundThere is an emerging consensus in developmental psychopathology that irritable youth are at risk for developing internalizing problems later in life. The current study explored if irritability in youth is multifactorial and the impact of irritability dimensions on psychopathology outcomes in adulthood.MethodsWe conducted exploratory factor analysis on irritability symptom items from a semi-structured diagnostic interview administered to a community sample of adolescents (ages 14–19; 42.7% male; 89.1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 44 publications
4
24
0
Order By: Relevance
“…Changes in irritability from preschool may reflect emotion development and regulation strategies. These developments presage internalizing and externalizing symptoms in pre-adolescence, when psychopathology is emerging and stabilizing (Class et al, 2019;Hawes et al, 2019;Jirsaraie et al, 2019). Additionally, early school age is a time of rapid gray matter volume maturation.…”
Section: Irritability Predits Clinical Outcomes/gray Matter Volumesmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in irritability from preschool may reflect emotion development and regulation strategies. These developments presage internalizing and externalizing symptoms in pre-adolescence, when psychopathology is emerging and stabilizing (Class et al, 2019;Hawes et al, 2019;Jirsaraie et al, 2019). Additionally, early school age is a time of rapid gray matter volume maturation.…”
Section: Irritability Predits Clinical Outcomes/gray Matter Volumesmentioning
confidence: 99%
“…This approach has elucidated unfolding patterns of symptoms that predict later psychopathology and provide insight into etiology and inform developmentally-based interventions (Cicchetti & Sroufe, 2000;Mittal & Wakschlag, 2017;Wakschlag et al, 2010). Within this context, a wealth of evidence demonstrates that atypical patterns of early irritability are predictive of emerging and subsequent psychopathology (Brotman et al, 2017;Carter et al, 2013;Fishburn et al, 2019;Hawes et al, 2019;Humphreys et al, 2019;Kessel et al, 2020;Smith et al, 2019;Wakschlag et al, 2010, IRRITABILITY PREDITS CLINICAL OUTCOMES/GRAY MATTER VOLUMES 4 2015a, 2019. Despite the promise of irritability to predict psychopathology, it is not yet clear how a general behavioral phenotype of excessive irritability translates into diverse, specific symptoms of psychopathology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that, compared to tonic irritability, phasic irritability was slightly more stable and heritable, and was a stronger indicator of the DMDD latent factor. Finally, Hawes et al (2019) conducted a factor analysis of the irritability items in the mood and disruptive behavior disorder sections of a diagnostic interview in a community sample of older adolescents and found two factors. One, reflecting three items from the mood disorders section, appeared to tap a tonic form of irritability, and the other, from three items in the disruptive behavior disorders section, seemed to reflect phasic irritability.…”
Section: Introductionmentioning
confidence: 99%
“…Youth irritability is broadly defined as a mood of low frustration–tolerance characterized by anger and temper outbursts (Brotman et al, 2017; Stringaris, Zavos, et al, 2012). Irritability, a transdiagnostic construct, constitutes one of the most common reasons for pediatric psychiatric evaluation and predicts adult depression, anxiety, suicidality, and lower educational and financial attainment (Brotman et al, 2017; Copeland et al, 2014; Hawes et al, 2020; Stringaris et al, 2009). Despite recent examination of youth irritability, little empirical data are available to guide researchers and clinicians in its assessment.…”
mentioning
confidence: 99%